The Influence of Creative Industries on the Russian Economy: Service, Hospitality, Advertising and Others - Levitskaia I. A., Konnov V. I., Domashina E. E., Emelianova V. A., Filimonov O. I., Miroshnikova T. K., Levchenko K. K., Levchenko T. P., Verna V. V., Ibragimov E. E., Radina O. I., Alekhina E. S., Volodina T. V. (The Influence of Creative Industries on the Russian Economy: Service, Hospitality, Advertising and Others, 2022)
the paper considers the problem of preserving water quality of rivers, in the channel and floodplain part of which gold deposits are developed by open-pit mining. As a result of the study we have developed the simplest engineering solutions for the design of environmental hydraulic structures. Designs of these structures were implemented in the project of Korolevskoye alluvial gold deposit in Transbaikalia. The operation of these structures during the washing of gold-bearing sands in the floodplain part of the Amazar River prevented the contamination of its water by industrial wastewater. The use of a water circulation system in the technological process and the filling of settling tanks with filtration and rainwater gave a positive water balance of the deposit. These measures prevented the impact of gold mining on the Mogocha municipal water intake located near the facility. As a result of technical and biological reclamation of disturbed lands during the development of the deposit, this area may serve as a recreational zone for Mogocha residents. Profitability of production and its economic efficiency are established by economic calculations given in the study.
Keywords: рентабельность; экономическая эффективность; economic efficiency; добыча золота; гидротехнические сооружения; рекреационная зона; природоохранные требования; profitability; gold mining; hydraulic structures; recreational area; environmental requirements